A Conceptual Model of Behavioral Factors Affecting the Adoption of E-government Services in Macao SAR - Iong, Kit Yeng (University of Saint Joseph, 2022)
Information and communication technologies (ICTs) are highly associated with the study of e-government, and many scholars believe that within the coming decades, government operation and policy decision-making cannot persist without the use of ICTs (Van Dijk, 2018). This thesis aims to generate a conceptual framework of the behavioral factors that could contribute to the acceleration of the implementation of e-government services in Macao SAR. Rather than regarding e-government services as a goal to be realized in traditional practice through evaluating the outcome, a process-oriented study was conducted. The e-government services are regarded as advanced tools in the 21st century to transform Macao into a smart city. The design of the process-oriented approach and the comparative study of four groups of Macao citizens' behavioral intentions are solidly supported by the research gaps identified in the literature review of e-government studies in an international perspective and the actual context of local Macao studies. Under the framework of the Theory of Planned Behavior (Ajzen, 1985, 1991), the behavioral factors of the general public and civil servants are investigated through a qualitative approach, and the findings are triangulated from various aspects. Firstly, a systematic literature review of TPB was conducted thoroughly to better understand the current study of e-government around the world. Secondly, a content and thematic analysis of the official documents and articles from local press media and research institutes related to the topic of e-government services was carried out to demonstrate a more comprehensive picture of the current problems of implementing iv and adopting e-services in Macao SAR. Observations in some government premises that provided e-services and 40 in-depth interviews were conducted to generate detailed and first-hand data. Key issues were extracted from the interviewees’ narratives and daily actual usages. Different conceptual models for different age groups and civil servant group were formed. Special attention was paid to analyzing the "hard-to-reach" groups' behavioral intentions. Research limitations identified from the previous literature were overcome partially in this study too. After comparing the similarities and differences, a new conceptual model of significant behavioral factors that affect the behavioral intentions in adopting e-government services was built. Results and findings from the analysis could be used to develop effective interventions by the government policymakers in responding to the behavioral change of the general public in the aspect of e-government services acceptance and adoption
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Adapting the Unified Theory of Acceptance and Use of Technology 2 (Utaut 2) to Explain Acceptance of Battery Electric Vehicles: Evidence From Macau - Lampo, Alessandro (University of Saint Joseph, 2020)
Vehicles solely powered by electricity are a major technological innovation that combines individual transportation needs and environmental sustainability, yet their market penetration is low. Research has traditionally indicated factors such as the vehicle’s purchasing price, driving range, and charging time as the main barriers to adoption. However, the decision to adopt a technology also depends on what the technology represents to the user; therefore, other factors may be important to explain individuals’ behavior. This study is a quantitative and cross-sectional look at the behavioral intention to adopt battery electric vehicles (BEVs) technology in the context of Macau. The research builds on the unified theory of acceptance and use of technology 2 (UTAUT 2) (Venkatesh et. al., 2012) to explain the characteristics of the local consumers. Besides the addition of image and environmental concern to the theoretical model, the study also put forward and evaluate the construct of technology show-off, an original measure of the visible and experiential characteristics of a technology. A sample of 236 Macau residents was analyzed by structural equation modeling (SEM). The analysis of the data supported the explanatory and predictive power of our model and helped to describe the idiosyncrasies of local residents. The results provide insights related to individual technology acceptance that could be useful in designing more accurate strategies and fostering the uptake of BEVs in Macau or markets that share similarities
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; Thesis and Dissertations PhD in Business Administration (D-BA); University of Saint Joseph

Enhancing Learning of Accounting for Non-Accounting students: Through Lens of Theory of Planned Behavior and Experiential Learning Styles - Lau, Meng Chan (University of Saint Joseph, 2020)
This thesis aims to explore how learning accounting for non-accounting major students could be enhanced through a comprehensive framework connecting individual attributes and learning approaches. While accounting is considered an important and mandatory discipline for business students, it is also considered a difficult subject which deters students’ engagement in the subject. Although the issue has been widely recognized, there are relatively less discussions on possible remedies. Learning accounting is a dynamic process that go beyond the traditional one-to-many learning and teaching settings, all factors revolving the students’ learning environment and process, altogether determine and affect the learning efficiencies. A meta-analysis was first performed to understand the standings of accounting education and to identify gaps within existing literatures in the field of management, accounting, tourism and general education researches. A documentary review on the curricula of all Macau HEI programs involving compulsory accounting courses was also conducted to understand the role and significance of accounting courses for non-accounting college students in Macau. Based on the literature review, this study borrows constructs from theory of planned behavior (TPB) models in its research framework. It attempts to provide a comprehensive framework to understand how students learn accounting efficiently by delving into individual learning styles of the students and their perceived helpfulness and self-efficacy, in respective to different learning techniques. Due to its exploratory nature, a mixed method of qualitative and quantitative methodology is adopted, where both focus group discussions and in-depth interviews are performed with non-accounting students to elicit understandings on student’s difficulties in learning accounting and their preferences for different learning styles. Then, a full-scale quantitative survey is conducted in a Macau higher education institute to assess the learning efficiencies of accounting in different situations. A triangulation with feedback from faculties and administrators are also elicited to provide alternate dimensions on the issues. With no surprise, there is no one best 3 teaching style or method for all students, this thesis contributes to accounting education research by provide a comprehensive diagnosis on the all-round learning stimulus and hindrance in learning accounting. At the end, recommendations are provided for accounting educators to emphasize on the uniqueness of students and to encourage a more dynamic and open environment for learning. Limitations of the studies are also discussed
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny Oliveros Lao (University of Saint Joseph, 2018)
This dissertation reports on a study which aims to add to the theoretical understanding of how social capital is transferred from one generation to the next in business families. Studies in the field of family business have emphasized the importance of succession for the survival of family businesses, but while the succession process and planning have been widely studied, the examination of social capital succession is scarce. As for the studies in family business’s social capital, the importance of social capital as a source of competitive advantage which already exists in business families have often been expressed, but there is a lack of research in the means of transferring this form of capital from the family business leaders to their successors. The study presented here addresses this gap in family business succession literature and social capital literature, explaining the means of transgenerational succession of social capital in family businesses. This is a qualitative research using the multiple case study method which aims to investigate the means of social capital transmission by comparing the cases of five different Chinese family businesses in Macau, which are in the succession process, with the successor currently managing the firm while the former generation business leaders are in the process of handing over the business and preparing for retirement. In doing so, this research offers a theoretical framework of explaining how social capital is transmitted from the incumbents to the successors throughout a five-stage succession process developed for this research. The forms of social capital that exists in family businesses are identified from previous literature, in order to clearly explain how these different forms of social capital are passed on from generation to generation based on the review on succession process introduced in published literature. A theoretical iii framework is formed from the two parent theories on family business succession and social capital, and is then verified empirically from five Chinese family businesses in Macau. The cases are developed through in-depth interviews with the incumbents and successors of the family businesses, informal interviews with stakeholders (including family members, business associates, non-family employees and customers), direct observation on the premises of the Chinese family businesses and secondary data, in order to study the process of intergenerational transmission of social capital in these Chinese family businesses
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph